2017
DOI: 10.1111/jdv.14073
|View full text |Cite
|
Sign up to set email alerts
|

Secukinumab administration by autoinjector maintains reduction of plaque psoriasis severity over 52 weeks: results of the randomized controlled JUNCTURE trial

Abstract: Self-administration of secukinumab using an autoinjector was associated with robust and sustained efficacy, a good safety profile and high acceptability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 22 publications
7
30
0
Order By: Relevance
“…Moreover, the majority of the patients found usage of an autoinjector easy or very easy, with no external help required. These observations are in agreement with those recently reported for the secukinumab autoinjector in the psoriasis JUNCTURE trial [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the majority of the patients found usage of an autoinjector easy or very easy, with no external help required. These observations are in agreement with those recently reported for the secukinumab autoinjector in the psoriasis JUNCTURE trial [ 23 ].…”
Section: Discussionsupporting
confidence: 93%
“…The JUNCTURE and FEATURE Phase III trials demonstrated that secukinumab administered by autoinjector pen or prefilled syringe continues to be well-tolerated at 1 year under the currently-approved dosing regimen. 19 , 37 No increased risk of injection-site reactions has been reported with secukinumab treatment with either method of administration. Patients who are able to comply with a regular monthly dosing regimen may benefit from secukinumab treatment due to its convenience over older biologic therapies, as well as for other reasons outlined in this manuscript.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical efficacy of secukinumab for psoriasis was evaluated with secondary endpoints assessing the usability and tolerability of an auto-injector pen in JUNCTURE, another randomized, double-blind, placebo-controlled Phase III trial. 19 The coprimary endpoints for this study were the proportions of patients achieving PASI 75 and IGA 0/1 at week 12 as compared to placebo. These coprimary endpoints were achieved, with significantly more patients treated with secukinumab achieving PASI 75 (86.7% vs 3.3%) and IGA 0/1 (73.3% vs 0%).…”
Section: Efficacy In Plaque Psoriasismentioning
confidence: 99%
See 1 more Smart Citation
“…Various factors contribute to NIEs. The chemical and physical properties of biologics that may contribute to NIEs are summarized in Table 3 (Abbvie, 2018;Eshtiaghi & Gooderham, 2018;European Medicines Agency, 2005Ferris et al, 2019;Immunex Corporation, 2016;Kavanaugh et al, 2012;Lacour et al, 2017;Nakamura et al, 2017;Papp et al, 2016;Sator, 2018;Savage, Wittmann, Mcgonagle, & Helliwell, 2015;US Food and Drug Administration, 2008, 2011, 2017a, 2017c, 2017d, 2018a, 2018b, 2018c, 2019a, 2019bvan der Heijde et al, 2018).…”
Section: Types Of Negative Injection Experiencesmentioning
confidence: 99%